Role of tissue-resident memory T cells in the pathophysiology of allergic contact dermatitis. Issue 4 (August 2021) - Lefevre, Marine-Alexia; Vocanson, Marc; Nosbaum, Audrey
Abstract : Purpose of review: We bring updated knowledge on tissue-resident memory T cells (TRM ), underlining their major role in the recurrence and the severity of allergic contact dermatitis (ACD). Recent findings: ACD is a frequently encountered skin disease. It is defined as a delayed-type hypersensitivity reaction initiated by the recruitment of antigen-specific T cells into the skin of sensitized patients. ACD lesions tend to develop on already-exposed areas and worsen over time. That clinical observation has raised questions on the contribution of TRM to ACD recurrence and severity. TRM are memory T cells that persist in peripheral tissues, such as the skin, without recirculating through the blood. These cells provide effective immune memory against pathogens, but they may also participate in the development or exacerbation of numerous inflammatory diseases, including skin allergies. Recent works have demonstrated a major role for TRM in ACD pathophysiology. Summary: In ACD, TRM accumulate preferentially at the allergen contact site during the sensitization phase. Thereafter, these cells cause a rapid and intense response to any new allergen exposure. They also play a key role in flare-ups of ACD and the chronicity and severity of the disease. These aspects suggest that TRM may have an interest as therapeutic targets.